The “Holodomor” and the Film “Bitter Harvest” are Fascist Lies - Furr, Grover (CounterPunch.org, 2017)
(Author’s note: In this article I rely heavily on the evidence cited in the research of Mark Tauger of West Virginia University. Tauger has spent his